Spider mite web mediates anti-predator behaviour - Lemos, Felipe; Sarmento, Renato Almeida; Pallini, Angelo; Dias, Cleide Rosa; Sabelis, Maurice W; Janssen, Arne (Experimental & applied acarology, 2010)
Herbivores suffer significant mortality from predation and are therefore subject to natural selection on traits promoting predator avoidance and resistance. They can employ an array of strategies to reduce predation, for example through changes in behaviour, morphology and life history. So far, the anti-predator response studied most intensively in spider mites has been the avoidance of patches with high predation risk. Less attention has been given to the dense web produced by spider mites, which is a complex structure of silken threads that is thought to hinder predators. Here, we investigate the effects of the web produced by the red spider mite, Tetranychus evansi Baker & Pritchard, on its interactions with the predatory mite, Phytoseiulus longipes Evans. We tested whether female spider mites recognize predator cues and whether these can induce the spider mites to produce denser web. We found that the prey did not produce denser web in response to such cues, but laid more eggs suspended in the web, away from the leaf surface. These suspended eggs suffered less from predation by P. longipes than eggs that were laid on the leaf surface under the web. Thus, by altering their oviposition behaviour in response to predator cues, females of T. evansi protect their offspring.